Electro-optic and dielectric study of the de Vries-type smectic- A phase exhibiting transitions to smectic- CA and smectic- C phases - PANARIN, YURI; VIJ, JAGDISH; FUKUDA, ATSUO; MANNA, UTTAM; SONG, JANG-KUN (My University, 2008)
Mixtures of different compositions of an antiferroelectric liquid crystal compound that exhibits direct smectic-A Sm-A -smectic-CA Sm-CA transition with a ferroelectric liquid crystal compound that exhibits Sm-A -smectic-C Sm-C transition are studied using electro-optics and dielectric spectroscopy. The results of optical texture, birefringence, and the tilt angle suggest that a part of the Sm-A phase is of de Vries type, since an increase in the tilt angle with decreasing temperature results in a reduction in the value of the birefringence in the Sm-A phase, whereas the birefringence at Sm-A to Sm-C transition goes up by 12.7%. The soft mode relaxation strength, the Landau coefficient of the temperature dependent term, and the other related parameters of the de Vries?type Sm-A -Sm-CA and Sm-A -Sm-C transitions are determined using the Landau theory of the second-order phase transition. For the Sm-A -Sm-C transition, we find that the soft mode relaxation strength decreases, the Landau coefficient increases, and the Curie-Weiss temperature range decreases with an increased ferroelectric composition in the mixture. These observations can be explained by assuming that with increased ferroelectric composition in the mixture, the layer shrinkage at the de Vries Sm-A -Sm-C transition increases. On comparing the results of de Vries?type Sm-A to Sm-CA and Sm-C transitions, we find that the soft mode dielectric strength and the other related Landau parameters of the deVries Sm-A phase are of the same order of magnitude for transitions from Sm-A to Sm-C and to Sm-CA except for the composition of the mixture where both Sm-C and Sm-CA transitions are stable and the phase diagram shows phase sequence Sm-A to Sm-C to Sm-CA.
PUBLISHED
Keywords: Electronic & Electrical Engineering